2016
DOI: 10.1007/s40279-016-0593-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-directed Exercise Programmes on Individuals with Type 2 Diabetes Mellitus: A Systematic Review Evaluating Their Effect on HbA1c and Other Metabolic Outcomes, Physical Characteristics, Cardiorespiratory Fitness and Functional Outcomes

Abstract: This review comprehensively summarised the effects planned self-directed exercise interventions had on individuals with T2DM. The review found that self-directed exercise was found to be beneficial for individuals with T2DM for improving glycosylated haemoglobin, physical characteristics, cardiorespiratory fitness, functional measures and other metabolic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 63 publications
3
30
0
5
Order By: Relevance
“…This finding could have relevance because it consolidates evidence supporting exercise as a powerful strategy for preventing type 2 diabetes, particularly in industrialised countries, which are suffering an epidemic of sedentariness. There is an extensive body of literature supporting the benefits of exercise training on cardiometabolic risk, and particularly on type 2 diabetes [47][48][49][50]. The main mechanisms behind this beneficial effect, in short, are that exercise increases insulin sensitivity in the trained muscle, and muscle work induces glucose uptake in the muscle [51].…”
Section: Discussionmentioning
confidence: 99%
“…This finding could have relevance because it consolidates evidence supporting exercise as a powerful strategy for preventing type 2 diabetes, particularly in industrialised countries, which are suffering an epidemic of sedentariness. There is an extensive body of literature supporting the benefits of exercise training on cardiometabolic risk, and particularly on type 2 diabetes [47][48][49][50]. The main mechanisms behind this beneficial effect, in short, are that exercise increases insulin sensitivity in the trained muscle, and muscle work induces glucose uptake in the muscle [51].…”
Section: Discussionmentioning
confidence: 99%
“…Self-directed long-term exercise programs have shown to be effective in improving health outcomes when T2D patients become more independent and self-motivated [62]. However, since dose and intensity of exercise need to be met in order to trigger the health-enhancing effects of exercise, the supervision of the training sessions becomes very important when short-term exercise programs are employed and/or patients are not yet independent.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that mitochondrial targeted antioxidants, resveratrol, exercise training, and caloric restriction help ameliorate the mitochondrial activity and insulin sensitivity in T2D (Apostolova & Victor, 2015;Escribano-Lopez et al, 2016;Larson-Meyer et al, 2006;Toledo et al, 2007). As shown in various studies, exercise can improve the insulin sensitivity and mitochondrial function (Byrne, Caulfield, & De Vito, 2017). In a study, researchers reported that endurance training with moderate and high intensity had a significant effect on the decreased levels of INFγ and TNFα in streptozotocin (STZ)-stimulated diabetic rats (Pasavand, Hosseini, & Farsi, 2018).…”
Section: Introductionmentioning
confidence: 96%